2021
DOI: 10.3390/pharmaceutics13101587
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab Dosing Individualization in Crohn’s Disease Guided by a Population Pharmacokinetic–Pharmacodynamic Model

Abstract: Ustekinumab is a monoclonal antibody used in Crohn’s disease (CD). Dose optimization in case of non-response and the role of pharmacokinetic–pharmacodynamic (PK-PD) monitoring remain unresolved dilemmas in clinical practice. We aimed to develop a population PK-PD model for ustekinumab in CD and simulate efficacy of alternative dosing regimens. We included 57 patients and recorded their characteristics during 32 weeks after starting with ustekinumab therapy. Serum ustekinumab concentration was prospectively mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…También se debe destacar que ninguno de los estudios incluyó la monitorización de niveles de fármaco en sangre. Teniendo en cuenta que este aspecto actualmente es una herramienta fundamental a la hora de toma de decisiones terapéuticas, parece importante destacar la necesidad de incluir esta variable en futuros estudios (15,16) .…”
Section: Discussionunclassified
“…También se debe destacar que ninguno de los estudios incluyó la monitorización de niveles de fármaco en sangre. Teniendo en cuenta que este aspecto actualmente es una herramienta fundamental a la hora de toma de decisiones terapéuticas, parece importante destacar la necesidad de incluir esta variable en futuros estudios (15,16) .…”
Section: Discussionunclassified
“…Several factors have been identified to accelerate the ustekinumab clearance in patients with IBD including increased body weight, lower albumin and immunogenicity (Figure 1) [41][42][43][44]. Other factors that can lead to a high clearance include prior exposure to biologics [42,43], increasing fat-free mass [43], male gender [42,44], Asian race [42] and higher CRP levels [42].…”
Section: Ustekinumabmentioning
confidence: 99%
“…71 This and other association studies have been supported in part by a population pharmacokinetic-pharmacodynamic model, which indicated that for patients not achieving remission by week 16 with standard dosing, intensifying the treatment to 4-weekly subcutaneous maintenance dosing could result in a 10% increment in remission rates by week 32. 72 However, for endoscopic response and remission, a similar model indicated only marginal benefit of treatment intensification. 73 Results from the ongoing RESCUE (Loss of RESponse to Ustekinumab Treated by Dose Escalation) study (NCT04245215), which is exploring the role of ustekinumab dose optimization in CD patients with secondary loss of response, will also contribute to our understanding of ustekinumab PK.…”
Section: Ustekinumabmentioning
confidence: 99%